The Influence of Work Motivation on Employee Performance with Compensation as an Intervening Variable in the Consortium Sorong Open Access Development Project PT. Hutama Karya (Persero) - PT. Gerbang Sarana Baja - Arjuharrido Rahmardiko, Tegha; Farida Ferine, Kiki (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The purpose of this research is to see the influence of work motivation on employee performance with compensation as an intervening variable in the Sorong Open Access Development Project of the PT. Hutama Karya (Persero) - PT. Gerbang Sarana Baja. This type of research uses quantitative, the research population is 70 employees and the sample used were all 70 employees at PT Hutama Karya (Persero) PT Pintu Sarana Baja. The data source used was a primary data source, data collection was carried out by distributing questionnaires, the research model used was phat analysis and the measuring tool was the Smart PLS version 3.3.3 application. The results of this research are as follows: Compensation has a positive and insignificant effect on employee performance with an original sample value of 0.325 and an ap value of 0.057. Work Motivation has a positive and significant effect on Employee Performance with an original sample of 0.423 and ap value of 0.004. Work Motivation has a positive and significant effect on Compensation with an original sample value of 0.876 and ap value of 0.000. Work Motivation has a positive and insignificant effect on Employee Performance through Compensation with an original sample value of 0.284 and ap value of 0.058.